An advanced high-energy sodium ion full battery based on nanostructured Na2Ti3O7/VOPO4 layered materials. Issue 11 (27th June 2016) - Li, Hongsen; Peng, Lele; Zhu, Yue; Chen, Dahong; Zhang, Xiaogang; Yu, Guihua
Abstract : A sodium ion full battery based on nanostructured Na2 Ti3 O7 /VOPO4 layered materials is developed, which exhibits attractive reversible capacity, outstanding rate capability and excellent cycling stability. Abstract : In virtue of the abundant sodium resources, sodium ion batteries (SIBs) have been considered to be one of the promising alternatives to lithium ion batteries (LIBs). However, current research concentrates mostly on sodium ion half-cells, and the development of sodium ion full cells with high performance remains a critical challenge. Here we rationally designed a full sodium-ion battery based on nanostructured Na2 Ti3 O7 and VOPO4 materials as the anodes and cathodes, owing to their advantageous electrochemical features. The full cell outputs one of the highest operating voltages close to 2.9 V and delivers a large reversible capacity of 114 mA h g −1 at a rate of 0.1C. It also shows outstanding rate capability (∼74 mA h g −1 at 2C rate) and excellent cycling stability (92.4% capacity retention after 100 cycles). A high energy density of 220 W h kg −1 is achieved, which is comparable to the state-of-the-art LIBs. Moreover, the temperature-dependent charge–discharge tests indicate excellent capacity retentions in a wide temperature range of −20 to 55 °C.